ANATOMICAL PREDICTORS IN HERNIA RECURRENCE - Abdurakhmanov, F.M.; Zukhurov, S.E. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Recurrence after ventral hernia repair remains a clinically significant and economically burdensome complication, particularly among elderly patients. In recent years, increasing attention has been paid to anatomical and morphometric factors that influence the stability of abdominal wall reconstruction. This review summarizes current evidence on anatomical predictors of recurrence, including aponeurosis thickness, diastasis recti, defect size and configuration, and mesh fixation zones. Emphasis is placed on the role of high-resolution imaging, intraoperative morphometry, and tissue quality evaluation in elderly individuals with recurrent hernias. Several risk stratification models incorporating these factors have been proposed, with promising results in reducing recurrence and optimizing surgical outcomes. Anatomical predictors should be considered a cornerstone in developing individualized, anatomy-informed surgical strategies for high-risk patients. Keywords: ventral hernia, recurrence, aponeurosis, morphometry, abdominal wall, elderly patients, anatomical risk factors